2015
DOI: 10.7556/jaoa.2015.076
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of Physicians in Civilian Medical Practice on Veterans’ Issues Related to Health Care

Abstract: The data indicated an overall moderate level of familiarity among civilian physicians with veterans' issues. The results did not reveal an overall high level of comfort with any issues included in the survey. More research is needed to determine reasons behind the findings and methods to improve civilian physician comfort with various veterans' issues.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 20 publications
0
16
0
Order By: Relevance
“…The increase in care fragmentation associated with more referrals to non-VA care may affect other aspects of care that are valued by WVs, such as their relationship with their VA PC providers, coordination of care, and receipt of care from providers experienced in caring for Veteran-specific issues. [35][36][37] Our findings point to provider communication and gender sensitivity as essential drivers of how patients view their care.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…The increase in care fragmentation associated with more referrals to non-VA care may affect other aspects of care that are valued by WVs, such as their relationship with their VA PC providers, coordination of care, and receipt of care from providers experienced in caring for Veteran-specific issues. [35][36][37] Our findings point to provider communication and gender sensitivity as essential drivers of how patients view their care.…”
Section: Discussionmentioning
confidence: 72%
“…While VA has sought greater oversight over the coordination of care between VA and community settings, how this coordination will be achieved and whether it will be tailored to WVs’ needs are still unknown. The increase in care fragmentation associated with more referrals to non‐VA care may affect other aspects of care that are valued by WVs, such as their relationship with their VA PC providers, coordination of care, and receipt of care from providers experienced in caring for Veteran‐specific issues …”
Section: Discussionmentioning
confidence: 99%
“…15 One study assessed community primary care providers’ perceptions and comfort with veterans’ healthcare problems, and found low comfort in addressing common issues. 16…”
Section: Introductionmentioning
confidence: 99%
“…However, based on published literature we can speculate that there is a knowledge gap in this area. For example, Fredricks and Nakazawa surveyed physicians (the majority were in primary care or internal medicine) to assess civilian physician knowledge of Veterans’ issues. The authors reported that despite providing care for a high percentage of Veterans, the physician participants recognized the need for more training on Veteran‐specific healthcare issues.…”
Section: Discussionmentioning
confidence: 99%